Biomolecular condensation orchestrates clathrin-mediated endocytosis in plants - Dragwidge, Jonathan Michael; Wang, Yanning; Brocard, Lysiane; De Meyer, Andreas; Hudeček, Roman; Eeckhout, Dominique; Grones, Peter; Buridan, Matthieu; Chambaud, Clément; Pejchar, Přemysl; Potocký, Martin; Winkler, Joanna; et al. (Nature cell biology, 2024)
Clathrin-mediated endocytosis is an essential cellular internalization pathway involving the dynamic assembly of clathrin and accessory proteins to form membrane-bound vesicles. The evolutionarily ancient TSET-TPLATE complex (TPC) plays an essential, but ill-defined role in endocytosis in plants. Here we show that two highly disordered TPC subunits, AtEH1 and AtEH2, function as scaffolds to drive biomolecular condensation of the complex. These condensates specifically nucleate on the plasma membrane through interactions with anionic phospholipids, and facilitate the dynamic recruitment and assembly of clathrin, as well as early- and late-stage endocytic accessory proteins. Importantly, condensation promotes ordered clathrin assemblies. TPC-driven biomolecular condensation thereby facilitates dynamic protein assemblies throughout clathrin-mediated endocytosis. Furthermore, we show that a disordered region of AtEH1 controls the material properties of endocytic condensates in vivo. Alteration of these material properties disturbs the recruitment of accessory proteins, influences endocytosis dynamics and impairs plant responsiveness. Our findings reveal how collective interactions shape endocytosis.
Keywords: endocytóza; klathrin; Cell Membrane; Clathrin; Endocytosis; buněčná membrána